GLOBALISASI DIGITAL DAN SHADOW EDUCATION DALAM EKONOMI PENDIDIKAN DASAR INDONESIA - Alhidayatuddiniyah T.W.; Rina Marlia; Yan Noviar Nasution (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Globalization has brought significant changes to the economics of primary education in Indonesia, particularly through the penetration of digital learning platforms and the expansion of shadow education. These two channels no longer function merely as pedagogical innovations, but have increasingly evolved into market mechanisms that shape education cost structures, household education consumption patterns, and the shifting roles among the state, schools, and non-state actors. This study aims to analyze the impact of globalization on the economics of primary education, identify forms of value leakage, and formulate contextual strategies for value capturing within the national education system. The research adopts a qualitative approach through a conceptual and policy-oriented literature review, drawing on systematic analysis of scholarly publications and reports from international organizations published between 2016 and 2026. The findings indicate that primary education is increasingly becoming a site of value leakage, where economic value generated from public funding, teachers’ labor, students’ learning time, and education data does not remain fully within the national education system but instead flows toward market actors through subscription-based services, platform dependency, and the commodification of learning. Shadow education is identified as an “invisible” form of globalization that reinforces inequality based on purchasing power, while primary education data emerges as a new strategic source of economic value that may undermine education sovereignty if not governed through robust regulatory frameworks. This study emphasizes the urgency of policy interventions to ensure that globalization in primary education remains oriented toward the public interest, equitable quality improvement, and social justice through platform regulation, education data protection, and strengthening schools’ capacity as the primary providers of basic education services.